Teacher factors as correlates of students' anxiety in junior secondary school mathematics: a study in school effectiveness (2011)
Students' mathematics anxiety is one of the problems in the secondary schools which make them not to perform optimally in mathematics achievement tests. Teachers have been seen as a single factor that can increase or reduce students' mathematics anxiety. Therefore this study examined the composite and relative contributions of five teacher factors (teacher qualification, gender, behaviour, expectation and attitude) to students' mathematics anxiety. The study adopted a survey a survey research of the expo facto type. A multi stage sampling technique was employed to obtain a sample of 54 JSS mathematics teachers and 1,620 JSS2 students in 54 schools in Oyo State. Two instruments used in this study were the Mathematics Anxiety Rating Scale (MARS) and Teacher Questionnaire (TQ). The data collected were subjected multiple regression analysis. The combination of the predictor variables: qualification, gender, behaviour, expectation and attitude explained 68.7 percent of the variance in students' anxiety in mathematics as shown by the coefficient of determination (R2 =0.838). The relative contributions of each of the three predictor variables shows that teacher attitude ( β=_0.282,p <0.05) had the highest contribution, teacher qualification(β= -0.133, p< 0.05), teacher classroom behaviour (β= -0.101, p< 0.05), teacher expectations (β= 0.102, p< 0.05) and teacher gender (β= 0.010, p>0.05). The potent predictor variable to students' mathematics anxiety is teacher attitude; therefore, teachers should be friendly in their approach as students tend to learn better in a tension free or friendly environment.